Development a Quantitative Framework for Multilayer Fuzzy Cognitive Maps by combining "Self-Organizing Map" and "Graph Theory and Matrix Approach" (SOM-GTMA) - Mohammad Ali Sangbor; Mohammad Reza Safi; Adel Azar; Masood Rabieh (مدیریت صنعتی, 2021)
Objective: The purpose of this study is to develop and improve the multilayer fuzzy cognitive maps in structuring and analysis of problems with high dimensions by providing a quantitative framework. Methods: In this study, the Self-Organizing Map method and Graph Theory and Matrix Approach has been combined in the multilayer fuzzy cognitive maps approach. Based on this approach, problem structuring is done by clustering and creating a multilayer structure for cognitive mapping. Results: The developed method in the present study has been used to analyze the problem of sustainable supply chain management achievement in the petrochemical industry. According to the results of data analysis based on the presented approach, "cooperation in the supply chain", "organizational development" and "management commitment to sustainable development" are the most effective factors in enabling sustainable supply chain management. Conclusion: Based on the method presented in the present study, the problem is modeled by clustering components and creating a multilayer structure for cognitive mapping. The method presented in the present study can model problems with a large number of intervening variables. The proposed method in this study can model problems with a high number of variables.